2009
DOI: 10.2478/s11658-009-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of human osteopontin increases cell proliferation and migration in human embryo kidney-293 cells

Abstract: Malignant tumors are characterized by dysregulated cell growth and the metastasis of secondary tumors. Numerous studies have documented that osteopontin (OPN) plays a key role in regulating tumor progression and metastasis. Here, we show that the overexpression of OPN in human embryo kidney-293 cells significantly increases both the level of cell proliferation, by provoking the G 1 /S transition, and the level of cell migration in vitro. These findings suggest that augmented OPN contributes to cell growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The final configuration of the protein thus influences its bioactivity. Although OPN performs beneficial functions, it has also been linked to cancer-associated mechanisms, such as tumorigenesis and proliferation (Liu et al, 2009), which may explain the metastatic ability of cancer cells.…”
Section: Proteomic Analysis and Immunodetection Of The Bovine Milk Osteopontin Isoformsmentioning
confidence: 99%
“…The final configuration of the protein thus influences its bioactivity. Although OPN performs beneficial functions, it has also been linked to cancer-associated mechanisms, such as tumorigenesis and proliferation (Liu et al, 2009), which may explain the metastatic ability of cancer cells.…”
Section: Proteomic Analysis and Immunodetection Of The Bovine Milk Osteopontin Isoformsmentioning
confidence: 99%
“…The significant increase of PCNA expression in the spleen of AQtreated animals suggests activation of immune system, and there was also an increase in serum osteopontin. Recent studies have shown that osteopontin is not only able to enhance cell proliferation in many tissues such as kidney, and prostate (Angelucci et al 2004;Liu et al 2009), but it also plays an important role in mediating hepatic inflammation and the ensuing liver toxicity (Ramaiah et al 2007). In addition, osteopontin was reported to be closely related to production of IL-17, a pro-inflammatory cytokine, during the pathogenesis of chronic hepatitis B and concanavalin A-induced hepatitis (Diao et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…OPN siRNA decreases mammary cell motility in vitro [147]. There is also evidence that OPN is capable of enhancing proliferation of various cell lines [155,156].…”
Section: Osteopontinmentioning
confidence: 99%